2007
DOI: 10.1136/jmg.2007.052670
|View full text |Cite
|
Sign up to set email alerts
|

Genotype phenotype study of familial haemophagocytic lymphohistiocytosis due to perforin mutations

Abstract: PRF1 mutations are spread over the functional domains. Specific mutations are strongly associated with Turkish, African American and Japanese ethnic groups. Later onset and residual cytotoxic function are observed in patients with at least one missense mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 52 publications
6
103
2
1
Order By: Relevance
“…[13] The prevalence and characteristics of PRF1 mutation may be different in different populations. [11,12] In this study, we found 11 novel mutations in 8 of 77 Chinese patients with lymphoma. We collected nails and/or hair follicles from 4 patients with PRF1 mutations.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[13] The prevalence and characteristics of PRF1 mutation may be different in different populations. [11,12] In this study, we found 11 novel mutations in 8 of 77 Chinese patients with lymphoma. We collected nails and/or hair follicles from 4 patients with PRF1 mutations.…”
Section: Discussionmentioning
confidence: 68%
“…[8] In addition to familial hemophagocytic lymphohistiocytosis due to PRF1 mutations, human lymphomas were also found to harbor PRF1 mutations in some cases. [9,10] The presence of PRF1 gene mutations may be different in different geographic regions and ethnic groups,[11,12] and little is known about the mutations in Chinese populations. Here we report our findings of mutations in the PRF1 gene and the association with EBV infection in Chinese patients with lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…58,[67][68][69] For example, the W374X mutation of PRF1 is common among patients of Turkish descent, a frameshift mutation 50delT leading to premature termination of PRF is virtually unique to patients of Central African descent 70 and the frameshift 1090.91delCT and 207delC originated from and are unique to SouthWestern Japan. 67,71 A number of disease incidents were also reported in other parts of Europe, but many of these patients were of Mediterranean origin.…”
Section: Genetics and Geoepidemiology Of Fhlmentioning
confidence: 99%
“…83,84 The most detrimental PRF1 mutations associated with minimal or no protein expression invariably present during early infancy, with a mean age of onset of 2 months. 3,69 If untreated, this form of FHL is always fatal within a few months or even weeks. By contrast, compound heterozygous PRF1 missense muta-tions are predominantly detected in older patients 3,69 and encode partially active PRF, which might enable patients to survive for a significant period of time before developing FHL.…”
Section: Perforin Deficiency and Human Cancermentioning
confidence: 99%
“…Perforin protein is relevant for cellular cytotoxicity mechanisms and its defect results in impaired antiviral defense and dysregulation of the apoptotic mechanisms causing FHL2. The most detrimental PRF1 mutations associated with minimal or no protein expression invariably present during early infancy, with a mean age of onset of 2 months, [2]. However, there have been reports of FHL2 cases with an age at onset in teens and adulthood [3][4][5].…”
Section: Introductionmentioning
confidence: 99%